1979
DOI: 10.2307/1366956
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Species Territoriality in Neotropical Foraging Flocks

Abstract: Multi-species flocking behavior in birds assumes a wide range of forms. At one extreme are casual feeding aggregations such as those of herons and seabirds (Sealy 1973, Baltz 1977, Kushlan 1977). Showing somewhat more social and temporal cohesiveness are the restless flocks of blackbirds or sandpipers that form and dissolve on a daily basis (Recher 1966, Recher and Recher 1969, Goss-Custard 1970, Page and Whitacre 1975, Burtt and Giltz 1977). Winter foraging groups of chickadees (Parus sp.) and their consorts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
221
3
10

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(246 citation statements)
references
References 29 publications
9
221
3
10
Order By: Relevance
“…In fact, feeding benefits are expected if insects are flushed by flock mates or due to copying behavior (Powell, 1985). In either case, a species would require the presence and close proximity of another species that employed a specific kind of foraging behavior (Krebs, 1973;Munn and Terborgh, 1979). Although the analysis on specific association between foraging species was beyond the scope of this study, during the observations on foraging tactics, no interaction suggested that a species foraged focusing another one, which might provide increased chances of prey capture.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In fact, feeding benefits are expected if insects are flushed by flock mates or due to copying behavior (Powell, 1985). In either case, a species would require the presence and close proximity of another species that employed a specific kind of foraging behavior (Krebs, 1973;Munn and Terborgh, 1979). Although the analysis on specific association between foraging species was beyond the scope of this study, during the observations on foraging tactics, no interaction suggested that a species foraged focusing another one, which might provide increased chances of prey capture.…”
Section: Discussionmentioning
confidence: 93%
“…Most other mixed flock members foraged solitarily, silently and closely focusing the vegetation. Apparently, this pattern of foraging behavior, at least, reduces the perception of flock partners, and predators as well (Munn and Terborgh, 1979;Sullivan, 1984a,b;Ragusa-Netto, 2002). One potential benefit associated with flock foraging is that an individual within a group may discover and use widely scattered, patchily distributed food more efficiently than if it had foraged independently.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations